Introduction to Cenozoic Biostratigraphy of Indonesia-SE Asia - J.T. (Han) van Gorsel; Peter Lunt; Robert Morley (Ikatan Ahli Geologi Indonesia, 2014)
An overview is presented of the current 'tools' of biostratigraphy and biofacies interpretation, as applied in the Cenozoic basins of Indonesia and Southeast Asia. We discuss previous work and historic developments of the biozonations and biofacies significance of the principal microfossil groups used in the region (foraminifera, calcareous nannofossils, palynology) and present the latest zonation charts and tables of key references. Brief reviews of work done on ostracodes, diatoms and radiolaria are also included.